Screening of women for intimate partner violence: a pilot intervention at an outpatient department in Tanzania - Rose M. Laisser; Lennarth Nyström; Gunilla Lindmark; Helen I. Lugina; Maria Emmelin (Taylor & Francis Group, 2011)
Intimate partner violence (IPV) is a public health problem in Tanzania with limited health care interventions.To study the feasibility of using an abuse screening tool for women attending an outpatient department, and describe how health care workers perceived its benefits and challenges.Prior to screening, 39 health care workers attended training on gender-based violence and the suggested screening procedures. Seven health care workers were arranged to implement screening in 3 weeks, during March–April 2010. For screening evaluation, health care workers were observed for their interaction with clients. Thereafter, focus group discussions (FGDs) were conducted with 21 health care workers among those who had participated in the training and screening. Five health care workers wrote narratives. Women's responses to screening questions were analyzed with descriptive statistics, whereas qualitative content analysis guided analysis of qualitative data.Of the 102 women screened, 78% had experienced emotional, physical, or sexual violence. Among them, 62% had experienced IPV, while 22% were subjected to violence by a relative, and 9.2% by a work mate. Two-thirds (64%) had been abused more than once; 14% several times. Almost one-quarter (23%) had experienced sexual violence. Six of the health care workers interacted well with clients but three had difficulties to follow counseling guidelines. FGDs and narratives generated three categories Just asking feels good implied a blessing of the tool; what next? indicated ethical dilemmas; and fear of becoming a 'women hospital’ only indicated a concern that abused men would be neglected.Screening for IPV is feasible. Overall, the health care workers perceived the tool to be advantageous. Training on gender-based violence and adjustment of the tool to suit local structures are important. Further studies are needed to explore the implications of including abuse against men and children in future screening.